1999
DOI: 10.1002/(sici)1097-0185(19991015)257:5<174::aid-ar6>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Coincident development of sesamoid bones and clues to their evolution

Abstract: Sesamoid bones form within tendons in regions that wrap around bony prominences. They are common in humans but variable in number. Sesamoid development is mediated epigenetically by local mechanical forces associated with skeletal geometry, posture, and muscular activity. In this article we review the literature on sesamoids and explore the question of genetic control of sesamoid development. Examination of radiographs of 112 people demonstrated that the relatively infrequent appearances of the fabella (in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
166
2
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(181 citation statements)
references
References 23 publications
9
166
2
4
Order By: Relevance
“…Kim et al (2009) reported that the lateral fabella, the distal os sesamoide tarsale and the cartilagines plantares disappear in denervated specimens of Hymenochirus boettgeri, and similar results were obtained by Mikic et al (2000), who found that menisci and sesamoids of the joints were absent in late stage, immobilized chick embryos. Although the origin of sesamoid bones is controversial (Pearson and Davin, 1921a,b;Sarin et al, 1999;Doherty, 2007;Doherty et al, 2010;Jerez et al, 2010;Ponssa et al, 2010), sesamoids are thought to arise as a result of mechanical stress (Carter et al, 1998;Sarin et al, 1999;Sarin and Carter, 2000). Although sesamoids are small, their developmental response to mechanical stress differs from that of carpal and tarsal bones.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (2009) reported that the lateral fabella, the distal os sesamoide tarsale and the cartilagines plantares disappear in denervated specimens of Hymenochirus boettgeri, and similar results were obtained by Mikic et al (2000), who found that menisci and sesamoids of the joints were absent in late stage, immobilized chick embryos. Although the origin of sesamoid bones is controversial (Pearson and Davin, 1921a,b;Sarin et al, 1999;Doherty, 2007;Doherty et al, 2010;Jerez et al, 2010;Ponssa et al, 2010), sesamoids are thought to arise as a result of mechanical stress (Carter et al, 1998;Sarin et al, 1999;Sarin and Carter, 2000). Although sesamoids are small, their developmental response to mechanical stress differs from that of carpal and tarsal bones.…”
Section: Discussionmentioning
confidence: 99%
“…Moles also develop a tibial sesamoid bone which, however, does not extend into the acropodial area as clearly as the radial sesamoid of the hand nor does it develop in association with a well-developed Msx2 expression domain as the radial sesamoid does. However, different sesamoid elements develop frequently coincidently [28]. Taking into account high incidences of certain sesamoids in conjunction with primary osteoarthritis [29], it was suggested that sesamoids tend to be linked in their appearance and that their presence may be owing to an increased tendency of endochondral ossification [28], perhaps manifested through genetic assimilation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the presence of an os peroneum has been shown to be genetically linked to the presence of a fabella. It has been suggested that since the peroneus longus is an adductor of the hallux, the lack of hallux opposability in homo sapiens may result in a lack of mechanical stimulus for formation and maintenance of an os peroneum, with changes in degree of plantar flexion in contrast to lower primates leading to lack of stimulus for formation of an os peroneum [5,8].…”
Section: Discussionmentioning
confidence: 99%